Pengaruh pesan edukasi kesehatan terhadap citra Rumah Sakit - Hakim, Alfi Fauzia; Munawaroh, Madinatul; Amini, Nadia Ushfuri; Annisa, Bilqis; Febrianti, Anti Restiani (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2022)
Background: Providing educational messages by health workers to patients and their families is a form of service provided by the hospital where the patient is treated and gets treatment. The quality of health services is currently getting high demands from people who are increasingly aware of health. Good service quality affects the high level of satisfaction of patients and their families as a public audience. This will also affect the image that is formed about the hospital. Purpose: To determine the effect of health education messages on the image of the Hospital institution. Methods: The method used is quantitative, with an explanatory survey approach. Results: The results of this study show that the results of the validity test on all questions in the questionnaire are valid, the results of the reliability test of the questionnaire state that they are reliable. The effect of giving health education messages in the form of tips directly on the image has a greater value, namely 11.4%, compared to information processing, both the central route, which is 4.5% and the peripheral route, which is 0.2%. Conclusion: There is an influence on health education messages in the form of tips on the image of Hospital institutions in Bandung Regency, West Java, both directly and through information processing, but it is very small and not significant.   Pendahuluan: Pemberian pesan-pesan edukasi oleh tenaga kesehatan kepada pasien dan keluarga pasien merupakan salah satu bentuk pelayanan yang diberikan rumah sakit tempat pasien tersebut berobat dan mendapatkan tindakan. Kualitas pelayanan kesehatan saat ini mendapatkan tuntutan yang tinggi dari masyarakat yang semakin sadar akan kesehatan. Kualitas pelayanan yang baik berpengaruh pada tingginya tingkat kepuasan pasien dan keluarga pasien sebagai publik khalayak. Hal ini akan berpengaruh juga pada citra yang terbentuk mengenai rumah sakit tersebut. Tujuan: Untuk mengetahui pengaruh pesan edukasi kesehatan terhadap citra lembaga Rumah Sakit. Metode: Metode yang digunakan adalah kuantitatif, dengan pendekatan survei eksplanatori. Hasil: Hasil dari penelitian ini memperlihatkan bahwa hasil uji validitas pada semua butir pertanyaan dalam kuesioner valid, hasil uji reliabilitas kuesioner menyatakan reliabel. Pengaruh pemberian pesan edukasi kesehatan berupa tips secara langsung terhadap citra memiliki nilai lebih besar, yaitu 11,4%, dibandingkan melalui pemrosesan informasi, baik jalur sentral yaitu 4,5% maupun jalur periferal yaitu 0,2%. Simpulan: Terdapat pengaruh pada pesan edukasi kesehatan berupa tips terhadap citra lembaga Rumah Sakit di Kabupaten Bandung, Jawa Barat, baik secara langsung maupun melalui pemrosesan informasi, namun sangat kecil dan tidak signifikan.